2012
DOI: 10.1117/12.917386
|View full text |Cite
|
Sign up to set email alerts
|

The SEMATECH Berkeley MET: demonstration of 15-nm half-pitch in chemically amplified EUV resist and sensitivity of EUV resists at 6.x-nm

Abstract: This document was prepared as an account of work sponsored by the United States Government. While this document is believed to contain correct information, neither the United States Government nor any agency thereof, nor The Regents of the University of California, nor any of their employees, makes any warranty, express or implied, or assumes any legal responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…BEUVL is considered as the next step following the 13.5 nm EUVL, and the resist materials for 6.x nm BEUVL has been discussed recently. 11,12,23,24 The resists selected were main-chain scission-type non-CA positive-tone resists such as poly (methyl methacrylate) (PMMA, M w = 350, 000, Aldrich), ZEP (1:1 copolymer of α-chloromethacrylate and α-methylstyrene, ZEP520A and ZEP7000, ZEON), and a polyhydroxystyrene (PHS)-based CA positive-tone resist OEBR-CAP112 (Tokyo Ohka Kogyo). The preparation of the samples, resist development, and exposures were performed at approximately 25…”
Section: -5mentioning
confidence: 99%
“…BEUVL is considered as the next step following the 13.5 nm EUVL, and the resist materials for 6.x nm BEUVL has been discussed recently. 11,12,23,24 The resists selected were main-chain scission-type non-CA positive-tone resists such as poly (methyl methacrylate) (PMMA, M w = 350, 000, Aldrich), ZEP (1:1 copolymer of α-chloromethacrylate and α-methylstyrene, ZEP520A and ZEP7000, ZEON), and a polyhydroxystyrene (PHS)-based CA positive-tone resist OEBR-CAP112 (Tokyo Ohka Kogyo). The preparation of the samples, resist development, and exposures were performed at approximately 25…”
Section: -5mentioning
confidence: 99%
“…1,4,18,19) A number of research groups have also shown the potential of unconventional inorganic 5,11) resists in further stretching these resolution limits. However, as discussed in previous chapters, concurrently achieving high resolution with the set of LWR/LER and sensitivity targets remains a challenge.…”
Section: Resist Processingmentioning
confidence: 99%
“…92,93) To improve lithography resolution, wavelength reduction has been an established procedure. The dependences of lithography resolution and sensitivity on the wavelength of the exposure tool have been reported in the wavelength range from 2 to 13.5 nm.…”
Section: Anisotropic Acid Diffusionmentioning
confidence: 99%
See 2 more Smart Citations